“Diseño y desarrollo de una aplicación móvil (UTChat) como medio de comunicación entre docentes-estudiantes de la Universidad Técnica de Cotopaxi Extensión La Maná.” - Benavides Zambrano, Carlos Damián (2021)
This research project aims at innovation with software development at the Technical University of Cotopaxi Extension La Mana in which studies were conducted allowing the design and development of a mobile application to improve communication between teacher-students of the aforementioned university. Through the use of the elicitation tools applied as the interview and the survey that allows to identify the problems, determine the requirements, also the needs to obtain the functionality of the application. On the fronted; side it was done with XML files that belongs to the Android Studio environment, on the backend; side the Java programming language was used and for the security of the information, as well as the storage of files it was taken into consideration the non-relational database manager system, i.e., NoSQL such as Firebase. In addition, it was important to study and establish the software engineering for the organization of the project processes; also, the use of agile methodologies that allow streamlining the development of each of the activities, for which the Scrum methodology was applied with its interactive incremental model; this allowed the analysis of the requirements, designs, development of the application, as well as testing, implementation and monitoring of this. The UTChat mobile application developed in Android Studio is according to the needs of users specified in the survey, it states that the institutional social network created will be compatible for smartphones that have the Android OS, with this application it will be possible to have an online institutional community, in the same way to control the information issued in the application, thus improving communication between teacher-students.